A high resolution small animal radiation research platform (SARRP) with x-ray tomographic guidance capabilities - Wong, John (2008)
PURPOSE: To demonstrate the CT imaging, conformal irradiation and treatment planning capabilities of a small animal radiation research platform (SARRP). METHODS: The SARRP employs a dual-focal spot, constant voltage x-ray source mounted on a gantry with a source-to-isocenter distance of 35 cm. Gantry rotation is limited to 120° from vertical. Eighty to 100 kVp x-rays from the smaller 0.4 mm focal spot are used for imaging. Both 0.4 mm and 3.0 mm focal spots operate at 225 kVp for irradiation. Robotic translate/rotate stages are used to position the animal. Cone-beam (CB) CT imaging is achieved by rotating the horizontal animal between the stationary x-ray source and a flat-panel detector. Radiation beams range from 0.5 mm in diameter to (60 × 60) mm(2). Dosimetry is measured with radio-chromic films. Monte Carlo dose calculations are employed for treatment planning. The combination of gantry and robotic stage motions facilitate conformal irradiation. RESULTS: The SARRP spans 3 ft × 4 ft × 6 ft (WxLxH). Depending on filtration, the isocenter dose outputs at 1 cm depth in water range from 22 to 375 cGy/min from the smallest to the largest radiation fields. The 20% to 80% dose fall-off spans 0.16 mm. CBCT with (0.6 × 0.6 × 0.6) mm(3) voxel resolution is acquired with less than 1 cGy. Treatment planning is performed at sub-mm resolution. CONCLUSIONS: The capability of the SARRP to deliver highly focal beams to multiple animal model systems provides new research opportunities that more realistically bridge laboratory research and clinical translation.